Improving reproductive & maternal health in rural Uganda Mothers should not die during delivery - Gateway Research Centre (Gateway Research Centre, 2019)
According to the World Health Organization (WHO), approximately 800 women die daily from preventable causes related to pregnancy and childbirth. Almost all of these deaths occur in developing countries with higher rates for women living in rural areas and among poorer communities. Everyday, 15 women die in Uganda from complications during pregnancy and childbirth-related causes. Many of these deaths are from causes that are largely preventable, with mothers’ deaths caused by four major factors namely; bleeding, hypertension, unsafe abortions and sepsis. Babies die mainly due to complications of prematurity, complications at birth and neonatal infections.